Femtosecond laser modification of an array of vertically aligned carbon nanotubes intercalated with Fe phase nanoparticles - Basaev, Alexander S. (2014)
Femtosecond lasers (FSL) are playing an increasingly important role in materials research, characterization, and modification. Due to an extremely short pulse width, interactions of FSL irradiation with solid surfaces attract special interest, and a number of unusual phenomena resulted in the formation of new materials are expected. Here, we report on a new nanostructure observed after the interaction of FSL irradiation with arrays of vertically aligned carbon nanotubes (CNTs) intercalated with iron phase catalyst nanoparticles. It was revealed that the FSL laser ablation transforms the topmost layer of CNT array into iron phase nanospheres (40 to 680 nm in diameter) located at the tip of the CNT bundles of conical shape. Besides, the smaller nanospheres (10 to 30 nm in diameter) are found to be beaded at the sides of these bundles. Some of the larger nanospheres are encapsulated into carbon shells, which sometime are found to contain CNTs. The mechanism of creation of such nanostructures is proposed.